IMPLEMENTASI PERATURAN BUPATI MAHAKAM ULU NOMOR 16 TAHUN 2018 TENTANG SISTEM PENGENDALIAN INTERN PEMERINTAH DI LINGKUNGAN PEMERINTAH DAERAH KABUPATEN MAHAKAM ULU - Gunarso, Willem Hendrik; Kusuma, Aji Ratna; Paselle, Enos (Jurnal Administrative Reform, 2023)
The purpose of this study is to describe and analyze the implementation of the Mahakam Ulu Regent's Regulation Number 16 of 2018 concerning the Implementation of the Government's Internal Control System in the Mahakam Ulu Regency Government and Identification of the factors that support and hinder it. This study uses a qualitative descriptive approach, using primary data and secondary data and processed through interactive model analysis. The implementation of the Mahakam Ulu Regent Regulation Number 16 of 2018 concerning the Implementation of SPIP in the Mahakam Ulu District Government has not been carried out optimally, and this can be seen in the communication aspect that has not been carried out properly, the resource aspect, especially the financial resources side, has only been carried out by the leading implementer (Inspectorate) but has not been implemented by the target group/group, meanwhile on the human resource side, improving the quality of its resources only focuses on improving the quality of the inspectorate's resources. However, in terms of quantity, it is still insufficient, as well as for the target group, it is not sufficient in terms of quality. Then terms supporting facilities and infrastructure are sufficient. Meanwhile, in the disposition aspect, namely the commitment and support of all relevant stakeholders, and the last is the organizational structure aspect which is carried out through the formation of a Task Force (Satgas) but has not been supported by an adequate Standard Operational Procedure (SOP).